Family Forward: a social work clinical trial promoting family adaptation following paediatric acquired brain injury. (7th June 2018) - Hickey, Lyndal; Anderson, Vicki; Hearps, Stephen; Jordan, Brigid
ABSTRACT: Objective : To test the efficacy of a family intervention Family Forward in promoting early adaptation following a child's acquired brain injury (ABI). Research design : Prospective, sequential comparison group design. Methods and procedures : Families of children ( n  = 47) diagnosed with ABI received Family Forward ( n  = 25): two family counselling sessions plus optional multi-family group session per week or Usual Care ( n  = 22) during their child's inpatient rehabilitation admission. Family adaptation outcomes were measured using Family Assessment Device (FAD-GF) and Family Management Measure (FAMM). Relationships between family psychosocial risk, social work interventions, and family adaptation outcomes were explored. Main outcomes and results : The Family Forward group endured longer hospital admissions ( FF M  = 56.4 days SD 46.1; p = 0.029 ), rehabilitation admissions ( FF M  = 33.3 days SD 29.0; p = 0.019 ) and reported poorer functioning pre-intervention FAD-GF ( FF M  = 1.626 SD = 0.391; UC M  = 1.491 SD 0.394) than the Usual Care group. No significant difference in family adaptation outcomes (FAD-GF) were detected; this suggests that the Family Forward intervention played a protective role in preventing deterioration in family functioning. The Family Forward group achieved superior outcomes in managing their child's care at home (FAMM Child Management Ability scale p = 0.029 ) and greater parental satisfaction in focusing on their child's care (FAMM Parent Mutuality scale p =  0.04) post-intervention. Conclusion : The Family Forward intervention moderated for poorer initial family functioning to achieve positive family adaptation outcomes.